## Factoring binomials using the difference of squares

### Step by step solution :

### Step 1 :

#### Equation at the end of step 1 :

(2^{2}•3x

^{2}) - 3 = 0

### Step 2 :

### Step 3 :

#### Pulling out like terms :

3.1 Pull out like factors :

12x^{2} - 3 = 3 • (4x^{2} - 1)

#### Trying to factor as a Difference of Squares :

3.2 Factoring: 4x^{2} - 1

Theory : A difference of two perfect squares, A^{2} - B^{2} can be factored into (A+B) • (A-B)

Proof : (A+B) • (A-B) =

A^{2} - AB + BA - B^{2} =

A^{2}- AB + AB - B^{2} =

A^{2} - B^{2}

Note : AB = BA is the commutative property of multiplication.

Note : - AB + AB equals zero and is therefore eliminated from the expression.

Check : 4 is the square of 2

Check : 1 is the square of 1

Check : x^{2} is the square of x^{1}

Factorization is : (2x + 1) • (2x - 1)

#### Equation at the end of step 3 :

3 • (2x + 1) • (2x - 1) = 0### Step 4 :

#### Theory - Roots of a product :

4.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

#### Equations which are never true :

4.2 Solve : 3 = 0

This equation has no solution.

A a non-zero constant never equals zero.

#### Solving a Single Variable Equation :

4.3 Solve : 2x+1 = 0

Subtract 1 from both sides of the equation :

2x = -1

Divide both sides of the equation by 2:

x = -1/2 = -0.500

#### Solving a Single Variable Equation :

4.4 Solve : 2x-1 = 0

Add 1 to both sides of the equation :

2x = 1

Divide both sides of the equation by 2:

x = 1/2 = 0.500

### Two solutions were found :

- x = 1/2 = 0.500
- x = -1/2 = -0.500

**Contents:** This page corresponds to **§****2.4 (p. 200)** of the text.

Suggested Problems from Text:

p. 212 #7, 8, 11, 15, 17, 18, 23, 26, 35, 38, 41, 43, 46, 47, 51, 54, 57, 60, 63, 66, 71, 72, 75, 76, 81, 87, 88, 95, 97

## Quadratic Equations

## Equations Involving Radicals

## Polynomial Equations of Higher Degree

## Equations Involving Fractional Expressions or Absolute Values

### Quadratic Equations

A quadratic equation is one of the form ax^{2} + bx + c = 0, where a, b, and c are numbers, and a is not equal to 0.

### Factoring

This approach to solving equations is based on the fact that if the product of two quantities is zero, then at least one of the quantities must be zero. In other words, if a*b = 0, then either a = 0, or b = 0, or both. For more on factoring polynomials, see the review section P.3 (p.26) of the text.

__Example 1.__

2x

^{2}- 5x - 12 = 0.(2x + 3)(x - 4) = 0.

2x + 3 = 0 or x - 4 = 0.

x = -3/2, or x = 4.

### Square Root Principle

If x^{2} = k, then x = ± sqrt(k).

__Example 2.__

x

^{2}- 9 = 0.x

^{2}= 9.x = 3, or x = -3.

__Example 3.__

__Example 4.__

x

^{2}+ 7 = 0.x

^{2}= -7.x = ± .

Note that = = , so the solutions are

x = ± , two complex numbers.

### Completing the Square

The idea behind completing the square is to rewrite the equation in a form that allows us to apply the square root principle.

__Example 5.__

x

^{2}+6x - 1 = 0.x

^{2}+6x = 1.x

^{2}+6x + 9 = 1 + 9.The 9 added to both sides came from squaring half the coefficient of x, (6/2)

^{2}= 9. The reason for choosing this value is that now the left hand side of the equation is the square of a binomial (two term polynomial). That is why this procedure is calledcompleting the square. [ The interested reader can see that this is true by considering (x + a)^{2}= x^{2}+ 2ax + a^{2}. To get "a" one need only divide the x-coefficient by 2. Thus, to complete the square for x^{2}+ 2ax, one has to add a^{2}.](x + 3)

^{2}= 10.Now we may apply the square root principle and then solve for x.

x = -3 ± sqrt(10).

__Example 6.__

2x

^{2}+ 6x - 5 = 0.2x

^{2}+ 6x = 5.The method of completing the square demonstrated in the previous example only works if the leading coefficient (coefficient of x

^{2}) is 1. In this example the leading coefficient is 2, but we can change that by dividing both sides of the equation by 2.x

^{2}+ 3x = 5/2.Now that the leading coefficient is 1, we take the coefficient of x, which is now 3, divide it by 2 and square, (3/2)

^{2}= 9/4. This is the constant that we add to both sides to complete the square.x

^{2}+ 3x + 9/4 = 5/2 + 9/4.The left hand side is the square of (x + 3/2). [ Verify this!]

(x + 3/2)

^{2}= 19/4.Now we use the square root principle and solve for x.

x + 3/2 = ± sqrt(19/4) = ± sqrt(19)/2.

x = -3/2 ± sqrt(19)/2 = (-3 ± sqrt(19))/2

So far we have discussed three techniques for solving quadratic equations. Which is best? That depends on the problem and your personal preference. An equation that is in the right form to apply the square root principle may be rearranged and solved by factoring as we see in the next example.

__Example 7.__

x^{2} = 16.

x^{2} - 16 = 0.

(x + 4)(x - 4) = 0.

x = -4, or x = 4.

In some cases the equation can be solved by factoring, but the factorization is not obvious.

The method of completing the square will always work, even if the solutions are complex numbers, in which case we will take the square root of a negative number. Furthermore, the steps necessary to complete the square are always the same, so they can be applied to the general quadratic equation

ax^{2} + bx + c = 0.

The result of completing the square on this general equation is a formula for the solutions of the equation called the Quadratic Formula.

### Quadratic Formula

The solutions for the equation ax

^{2}+ bx + c = 0 are

We are saying that completing the square always works, and we have completed the square in the general case, where we have a,b, and c instead of numbers. So, to find the solutions for any quadratic equation, we write it in the standard form to find the values of a, b, and c, then substitute these values into the Quadratic Formula.

One consequence is that you never have to complete the square to find the solutions for a quadratic equation. However, the process of completing the square is important for other reasons, so you still need to know how to do it!

**Examples using the Quadratic Formula:**

__Example 8.__

2x

^{2}+ 6x - 5 = 0.In this case, a = 2, b = 6, c = -5. Substituting these values in the Quadratic Formula yields

Notice that we solved this equation earlier by completing the square.

Note: There are two real solutions. In terms of graphs, there are two intercepts for the graph of the function f(x) = 2x^{2}+ 6x - 5.

__Example 9.__

4x

^{2}+ 4x + 1 = 0In this example a = 4, b = 4, and c = 1.

There are two things to notice about this example.

- There is only one solution. In terms of graphs, this means there is only one x-intercept.
- The solution simplified so that there is no square root involved. This means that the equation could have been solved by factoring. (All quadratic equations
canbe solved by factoring! What I mean is it could have been solvedeasilyby factoring.)4x

^{2}+ 4x + 1 = 0.(2x + 1)

^{2}= 0.x = -1/2.

__Example 10.__

x

^{2}+ x + 1 = 0a = 1, b = 1, c = 1

Note:There are no real solutions. In terms of graphs, there are no intercepts for the graph of the function f(x) = x^{2}+ x + 1. Thus, the solutions are complex because the graph of y = x^{2}+ x + 1 has no x-intercepts.

The expression under the radical in the Quadratic Formula, b^{2} - 4ac, is called the discriminant of the equation. The last three examples illustrate the three possibilities for quadratic equations.

1. Discriminant > 0. Two real solutions.

2. Discriminant = 0. One real solution.

3. Discriminant < 0. Two complex solutions.

**Notes on checking solutions**

None of the techniques introduced so far in this section can introduce extraneous solutions. (See example 3 from the Linear Equations and Modeling section.) However, it is still a good idea to check your solutions, because it is very easy to make careless errors while solving equations.

The algebraic method, which consists of substituting the number back into the equation and checking that the resulting statement is true, works well when the solution is "simple", but it is not very practical when the solution involves a radical.

For instance, in our next to last example, 4x

^{2}+ 4x + 1 = 0, we found one solution x = -1/2.The algebraic check looks like

4(-1/2)

^{2}+4(-1/2) + 1 = 0.4(1/4) - 2 + 1 = 0.

1 - 2 + 1 = 0.

0 = 0. The solution checks.

In the example before that, 2x

^{2}+ 6x - 5 = 0, we found two real solutions, x = (-3 ± sqrt(19))/2. It is certainly possible to check this algebraically, but it is not very easy. In this case either a graphical check, or using a calculator for the algebraic check are faster.First, find decimal approximations for the two proposed solutions.

(-3 + sqrt(19))/2 = 0.679449.

(-3 - sqrt(19))/2 = -3.679449.

Now use a graphing utility to graph y = 2x

^{2}+ 6x - 5, and trace the graph to find approximately where the x-intercepts are. If they are close to the values above, then you can be pretty sure you have the correct solutions. You can also insert the approximate solution into the equation to see if both sides of the equation give approximately the same values. However, you still need to be careful in your claim that your solution is correct, since it is not the exact solution.Note that if you had started with the equation 2x

^{2}+ 6x - 5 = 0 and gone directly to the graphing utility to solve it, then you would not get the exact solutions, because they are irrational. However, having found (algebraically) two numbers that you think are solutions, if the graphing utility shows that intercepts are very close to the numbers you found, then you are probably right!

*Exercise 1:*

Solve the following quadratic equations.

(a) 3x

^{2}-5x - 2 = 0. Answer(b) (x + 1)

^{2}= 3. Answer(c) x

^{2}= 3x + 2. Answer

**Return to Contents**

### Equations Involving Radicals

Equations with radicals can often be simplified by raising to the appropriate power, squaring if the radical is a square root, cubing for a cube root, etc. This operation can introduce extraneous roots, so all solutions must be checked.

If there is only one radical in the equation, then before raising to a power, you should arrange to have the radical term by itself on one side of the equation.

__Example 11.__

Now that we have isolated the radical term on the right side, we square both sides and solve the resulting equation for x.

Check:x = 0

When we substitute x = 0 into the original equation we get the statement 0 = 2, which is not true!

So, x = 0

is not a solution.x = 3

When we substitute x = 3 into the original equation, we get the statement 3 = 3. This is true, so x = 3

is a solution.

Solution: x = 3.

Note:The solution is the x-coordinate of the intersection point of the graphs of y = x and y = sqrt(x+1)+1.

Look at what would have happened if we had squared both sides of the equation *before* isolating the radical term.

This is worse than what we started with!

If there is more than one radical term in the equation, then in general, we cannot eliminate all radicals by raising to a power one time. However, we can *decrease* the number of radical terms by raising to a power.

If the equation involves more than one radical term, then we still want to isolate one radical on one side and raise to a power. Then we repeat that process.

__Example 12.__

Now square both sides of the equation.

This equation has only one radical term, so we have made progress! Now isolate the radical term and then square both sides again.

Check:Substituting x = 5/4 into the original equation yields

sqrt(9/4) + sqrt(1/4) = 2.

3/2 + 1/2 = 2.

This statement is true, so x = 5/4 is a solution.

**Note on checking solutions:**

The algebraic check was easy to do in this case. However, the graphical check has the advantage of showing that there are no solutions that we have not found, at least within the scope of the viewing rectangle. The solution is the x-coordinate of the intersection point of the graphs of y = 2 and y = sqrt(x+1)+sqrt(x-1).

*Exercise 2:*

Solve the equation sqrt(x+2) + 2 = 2x. Answer

**Return to Contents**

### Polynomial Equations of Higher Degree

We have seen that any degree two polynomial equation (quadratic equation) in one variable can be solved with the Quadratic Formula. Polynomial equations of degree greater than two are more complicated. When we encounter such a problem, then either the polynomial is of a special form which allows us to factor it, or we must approximate the solutions with a graphing utility.

### Zero Constant

One common special case is where there is no constant term. In this case we may factor out one or more powers of x to begin the problem.

__Example 13.__

2x

^{3}+ 3x^{2}-5x = 0.x (2x

^{2}+ 3x -5) = 0.Now we have a product of x and a quadratic polynomial equal to 0, so we have two simpler equations.

x = 0, or 2x

^{2}+ 3x -5 = 0.The first equation is trivial to solve. x = 0 is the only solution. The second equation may be solved by factoring.

Note:If we were unable to factor the quadratic in the second equation, then we could have resorted to using the Quadratic Formula. [Verify that you get the same results as below.]x = 0, or (2x + 5)(x - 1) = 0.

So there are three solutions: x = 0, x = -5/2, x = 1.

Note:The solution is found from the intercepts of the graphs of f(x) = 2x^{3}+ 3x^{2}-5x.

### Factor by Grouping

__Example 14.__

x

^{3}-2x^{2}-9x +18 = 0.The coefficient of x

^{2}is -2 times that of x^{3}, and the same relationship exists between the coefficients of the third and fourth terms. Group terms one and two, and also terms three and four.x

^{2}(x - 2) - 9 (x - 2) = 0.These groups share the common factor (x - 2), so we can factor the left hand side of the equation.

(x - 2)(x

^{2}- 9) = 0.Whenever we find a product equal to zero, we obtain two simpler equations.

x - 2 = 0, or x

^{2}- 9 = 0.x = 2, or (x + 3)(x - 3) = 0.

So, there are three solutions, x = 2, x = -3, x = 3.

Note:These solutions are found from the intercepts of the graph of f(x) = x^{3}-2x^{2}-9x +18.

### Quadratic in Form

__Example 15.__

x

^{4}- x^{2}- 12 = 0.This polynomial is not quadratic, it has degree four. However, it can be thought of as quadratic in x

^{2}.(x

^{2})^{2}-(x^{2}) - 12 = 0.It might help you to actually substitute z for x

^{2}.z

^{2}- z - 12 = 0 This is a quadratic equation in z.(z - 4)(z + 3) = 0.

z = 4 or z = -3.

We are not done, because we need to find values of x that make the original equation true. Now replace z by x

^{2}and solve the resulting equations.x

^{2}= 4.x = 2, x = -2.

x

^{2}= -3.x =

i, or x = -i.So there are four solutions, two real and two complex.

Note:These solutions are found from the intercepts of the graph of f(x) = x^{4}- x^{2}- 12.

A graph of f(x) = x^{4}- x^{2}- 12 and a zoom showing its local extrema.

*Exercise 3:*

Solve the equation x

^{4}- 5x^{2}+ 4 = 0. Answer

**Return to Contents**

### Equations Involving Fractional Expressions or Absolute Values

__Example 16.__

The least common denominator is x(x + 2), so we multiply both sides by this product.

This equation is quadratic. The Quadratic Formula yields the solutions

Checking is necessary because we multiplied both sides by a variable expression. Using a graphing utility we see that both of these solutions check. The solution is the x-coordinate of the intersection point of the graphs of y = 1 and y = 2/x-1/(x+2).

__Example 17.__

5 | x - 1 | = x + 11.

The key to solving an equation with absolute values is to remember that the quantity inside the absolute value bars could be positive or negative. We will have two separate equations representing the different possibilities, and all solutions must be checked.

Suppose x - 1 >= 0. Then | x - 1 | = x - 1, so we have the equationCase 1.5(x - 1) = x + 11.

5x - 5 = x + 11.

4x = 16.

x = 4, and this solution checks because 5*3 = 4 + 11.

Suppose x - 1 < 0. Then x - 1 is negative, so | x - 1 | = -(x - 1). This point often confuses students, because it looks as if we are saying that the absolute value of an expression is negative, but we are not. The expression (x - 1) is already negative, so -(x - 1) is positive.Case 2.Now our equation becomes

-5(x - 1) = x + 11.

-5x + 5 = x + 11.

-6x = 6.

x = -1, and this solution checks because 5*2 = -1 + 11.

If you use the Java Grapher to check graphically, note that abs() is absolute value, so you would graph

and look at x-intercepts, or you can find the solution as the x-coordinates of the intersection points of the graphs of y = x+11 and y = 5*abs(x-1).

**Exercise 4:**

(a) Solve the equation Answer

(b) Solve the equation | x - 2 | = 2 - x/3 Answer

**Return to Contents**

## Simplification or other simple results

### Step 1 :

#### Equation at the end of step 1 :

(2^{2}•3x

^{2}) - 3

### Step 2 :

### Step 3 :

#### Pulling out like terms :

3.1 Pull out like factors :

12x^{2} - 3 = 3 • (4x^{2} - 1)

#### Trying to factor as a Difference of Squares :

3.2 Factoring: 4x^{2} - 1

Theory : A difference of two perfect squares, A^{2} - B^{2} can be factored into (A+B) • (A-B)

Proof : (A+B) • (A-B) =

A^{2} - AB + BA - B^{2} =

A^{2}- AB + AB - B^{2} =

A^{2} - B^{2}

Note : AB = BA is the commutative property of multiplication.

Note : - AB + AB equals zero and is therefore eliminated from the expression.

Check : 4 is the square of 2

Check : 1 is the square of 1

Check : x^{2} is the square of x^{1}

Factorization is : (2x + 1) • (2x - 1)

### Final result :

3 • (2x + 1) • (2x - 1)## Linear equations with one unknown

### Step by step solution :

### Step 1 :

#### Equation at the end of step 1 :

(2^{2}•3x

^{2}) - 20x = 0

### Step 2 :

### Step 3 :

#### Pulling out like terms :

3.1 Pull out like factors :

12x^{2} - 20x = 4x • (3x - 5)

#### Equation at the end of step 3 :

4x • (3x - 5) = 0### Step 4 :

#### Theory - Roots of a product :

4.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

#### Solving a Single Variable Equation :

4.2 Solve : 4x = 0

Divide both sides of the equation by 4:

x = 0

#### Solving a Single Variable Equation :

4.3 Solve : 3x-5 = 0

Add 5 to both sides of the equation :

3x = 5

Divide both sides of the equation by 3:

x = 5/3 = 1.667

### Two solutions were found :

- x = 5/3 = 1.667
- x = 0

## Answer 12x^2

## Algebra Calculator Tutorial

This is a tutorial on how to use the **Algebra Calculator**, a step-by-step calculator for algebra.

### Solving Equations

First go to the Algebra Calculator main page. In the Calculator's text box, you can enter a math problem that you want to calculate.

For example, try entering the equation 3x+2=14 into the text box.

After you enter the expression, Algebra Calculator will print a step-by-step explanation of how to solve 3x+2=14.

### Examples

To see more examples of problems that Algebra Calculator understands, visit the Examplespage. Feel free to try them now.### Math Symbols

If you would like to create your own math expressions, here are some symbols that Algebra Calculator understands:

**+** (Addition) **-** (Subtraction) ***** (Multiplication) **/** (Division) **^** (Exponent: "raised to the power")

### Graphing

To graph an equation, enter an equation that starts with "y=" or "x=". Here are some examples: y=2x^2+1, y=3x-1, x=5, x=y^2.

To graph a point, enter an ordered pair with the x-coordinate and y-coordinate separated by a comma, e.g., (3,4).

To graph two objects, simply place a semicolon between the two commands, e.g., y=2x^2+1; y=3x-1.

### Polynomials

Algebra Calculator can simplify polynomials, but it only supports polynomials containing the variable x.

Here are some examples: x^2 + x + 2 + (2x^2 - 2x), (x+3)^2.

### Evaluating Expressions

Algebra Calculator can evaluate expressions that contain the variable x.

To evaluate an expression containing x, enter the expression you want to evaluate, followed by the @ sign and the value you want to plug in for x. For example the command 2x @ 3 evaluates the expression 2x for x=3, which is equal to 2*3 or 6.

Algebra Calculator can also evaluate expressions that contain variables x and y. To evaluate an expression containing x and y, enter the expression you want to evaluate, followed by the @ sign and an ordered pair containing your x-value and y-value. Here is an example evaluating the expression xy at the point (3,4): xy @ (3,4).

### Checking Answers For Solving Equations

Just as Algebra Calculator can be used to evaluate expressions, Algebra Calculator can also be used to check answers for solving equations containing x.

As an example, suppose we solved 2x+3=7 and got x=2. If we want to plug 2 back into the original equation to check our work, we can do so: 2x+3=7 @ 2. Since the answer is right, Algebra Calculator shows a green equals sign.

If we instead try a value that doesn't work, say x=3 (try 2x+3=7 @ 3), Algebra Calculator shows a red "not equals" sign instead.

To check an answer to a system of equations containing x and y, enter the two equations separated by a semicolon, followed by the @ sign and an ordered pair containing your x-value and y-value. Example: x+y=7; x+2y=11 @ (3,4).

### Tablet Mode

If you are using a tablet such as the iPad, enter Tablet Mode to display a touch keypad.

### Related Articles

Because he was like your dog, even though he was on a chain, but still had a good owner. I am still on your chain, although you untied it a long time ago. And imagine the situation. with a collar and an untied chain I'm walking around the city, everyone is staring at me.

### Similar news:

- Lens of truth
- 2008 honda accord thermostat
- Volvo xc60 2015 specs
- Palm tree tattoos
- Kratom benefits list
- Hp envy touchsmart
- Ford dealership moultrie ga
- Back of postcard rules

Get out. You can't calm me down with such lies. Go away.

**18075**18076 18077